1978
DOI: 10.1007/bf00670845
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine development, feto-placental function and pregnancy outcome after induction of ovulation with bromoergocryptine

Abstract: 18 pregnancies occurred after treatment with bromoergocryptine in 17 patients who wished to conceive, but who suffered from anovulation of varying aetiology. The course of 15 pregnancies was uneventful. Three pregnancies ended in abortion. Nine of the 17 women had hyperprolactinemic amenorrhea. Furthermore, one woman had normoprolactinemic post-pill amenorrhea, another normoprolactinemic anovulatory oligomenorrhea and a third normoprolactinemic anovulatory regular menstruations. With the exception of one woman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In these patients Pepperell et al (1 977) and Thomas et al (1 977) found decreased levels of urinary pregnanediol or serum progesterone and oestradiol, but only during the last weeks of the first trimester. These findings could not be substantiated by Clemens et al (1978), and since the corpus luteum is the dominant source of steroid during the first 9 weeks of pregnancy (Yoshimi e t a / . , 1969; Holmdal et a/., 1971) there is no evidence that hyperprolactinaemia can impair the corpus luteum of early pregnancy.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In these patients Pepperell et al (1 977) and Thomas et al (1 977) found decreased levels of urinary pregnanediol or serum progesterone and oestradiol, but only during the last weeks of the first trimester. These findings could not be substantiated by Clemens et al (1978), and since the corpus luteum is the dominant source of steroid during the first 9 weeks of pregnancy (Yoshimi e t a / . , 1969; Holmdal et a/., 1971) there is no evidence that hyperprolactinaemia can impair the corpus luteum of early pregnancy.…”
Section: Discussionmentioning
confidence: 98%
“…A clinical parallel is found in hyperprolactinaemic patients who conceive with suppressed prolactin levels on bromocriptine. Clinically these pregnancies have a normal development during early gestation (Pepperell et a/., 1977;Thomas et a/., 1977;Clemens et a/., 1978;Griffith et a/., 1978;Thorner et a/., 1979) even though serum prolactin is low during treatment, but rapidly increases above normal early pregnancy levels following cessation of therapy. In these patients Pepperell et al (1 977) and Thomas et al (1 977) found decreased levels of urinary pregnanediol or serum progesterone and oestradiol, but only during the last weeks of the first trimester.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations